Direct Decarbonization Model for Handling Equipment at Jamrud Terminal Using a Combination Method of Default Emission Factors (DEF) and Direct Monitoring of Greenhouse Gas Emissions (DMGGE) - Salim, Sarwo Edy Agus; Gurning , Saut; Nugroho, Taufik Fajar; Gopinath (International Journal of Marine Engineering Innovation and Research, 2025)
As one of the largest archipelagic countries with a port system that supports more than 90% of its trade volume, Indonesia faces an urgent need to implement the green port concept to minimize environmental impacts, improve energy efficiency, and support national decarbonization commitments. One example is the Tanjung Perak Port, specifically the Jamrud Terminal in Surabaya. This study takes Jamrud Terminal—which provides loading and unloading services for general cargo, passengers, and dry bulk—as a case study. The terminal operates 24 hours a day and thus undoubtedly contributes to pollution, including air pollution from exhaust gas emissions, which are increasing due to a 23.06% growth in vehicle handling activities throughout 2024. Quantifying greenhouse gas (GHG) emissions from the main quay equipment and supporting equipment at Jamrud Terminal is crucial to assess current fossil fuel energy consumption and propose technological interventions to enhance energy efficiency and reduce GHG intensity from fuel usage.This paper aims to identify and calculate the existing direct emissions, analyze the trend of GHG emissions from port equipment, and develop a projection model of GHG emissions from equipment at Jamrud Terminal. The equipment includes Harbour Mobile Cranes, Harbour Portal Cranes, Excavators, Forklifts, Mobile Sweepers, Wheel Loaders, and Generators, with data sourced from primary records of fuel consumption supplied during the 2022 to 2024 period. GHG emissions projection is modeled using the Default Emission Factors method and the Direct Monitoring of Greenhouse Gas Emissions (DMGGE) approach. The results show that from 2022 to 2024, Jamrud Terminal emitted approximately 7.1 tons of CO2eq from stationary combustion and 5,378.88 tons of CO2eq from mobile combustion.A future decarbonization scenario developed in this study indicates that if the terminal transitions to electrification and the use of alternative energy fuels such as LPG or CNG, CO2 emissions could be reduced by as much as 98.6%. The results of this paper will be valuable in formulating effective planning, policies, and strategies to reduce GHG emissions from direct sources related to both main and supporting equipment at Jamrud Terminal.